Russian Literature in the Journal “Prostor” 1991-1999: Publications, Reviews, Scientific Articles - Nikita Yu. Okutin (Polylinguality and Transcultural Practices)
The study is devoted to the phenomenon of Kazakhstani “thick” magazine “Prostor” in the period from 1991 to 1999. For the first time the magazine is considered as a cultural mediator that contributed to the preservation of ties between Russian and Kazakh cultural fields in the post-Soviet period. The publication activity of the journal, which presented to the reader the unknown and forgotten heritage of the Silver Age, previously banned Soviet writers and representatives of the Russian emigration, is analyzed. The review of literary and literary-critical publications on the pages of the journal is given, which testify to the undying interest of Kazakhstani science to Russian literature in the new era. The role of “Prostor” in preserving a unified Russian-Kazakh cultural field in the post-Soviet period, maintaining the stability of the common intellectual and scientific space is emphasized.